Knowledge based full aperture polishing - Schneckenburger Max; Shaikh Ayaan; Algac Ufuc; Mewis Jan (Journal of the European Optical Society-Rapid Publications)
Understanding and controlling of the polishing process on conventional NC (Numerical Control) machines is an important step to optimize production, reduce machine time and increase production quality. Nevertheless, due to the high number of process parameters, polishing is not understood and is almost exclusively applied empirically. The work presented in this paper shows a production-ready attachment to a lever arm polishing machine, which can be used to map the removal of material using relative speed. Calculated relative velocity and observed material removal indicate a correlation of 31.5%. This is a first step towards the complete automation of the polishing process in order to save process times, increase repeatability and avoid handling errors. It is planned to focus other polishing parameters in the future and improve the removal model.